2003
DOI: 10.1081/ppt-120017921
|View full text |Cite
|
Sign up to set email alerts
|

Flash Vacuum Pyrolysis of Low Density Polyethylene in a Free-Fall Reactor

Abstract: Polyethylene (PE) is the principal component of postconsumer plastic wastes. It is important to develop chemical techniques to decompose PE with a view to recycling and production of compounds that are valuable as fuel or industrial raw materials. The most common reactors in polymer pyrolysis are fluidized-bed types. Free-fall reactors do not suffer the disadvantages of fluidized beds related to inert gas employment. This flash pyrolysis study has shown that low density polyethylene (LDPE) can be continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, there are other works containing different raw materials such as coal, polymer and biomass. Karaduman et al [20] reported for pyrolysis of LDPE that both the liquid and gas yield produced in the free-fall reactor increased with temperature raising from 750 to 875 8C. The liquid and gas yield produced at a temperature of 750 8C, particle sizes of 150-75 mm and feed rate of 2 g min À1 were found as 6 and 37 wt.%, respectively.…”
Section: Effect Of Pyrolysis Temperaturementioning
confidence: 94%
See 3 more Smart Citations
“…However, there are other works containing different raw materials such as coal, polymer and biomass. Karaduman et al [20] reported for pyrolysis of LDPE that both the liquid and gas yield produced in the free-fall reactor increased with temperature raising from 750 to 875 8C. The liquid and gas yield produced at a temperature of 750 8C, particle sizes of 150-75 mm and feed rate of 2 g min À1 were found as 6 and 37 wt.%, respectively.…”
Section: Effect Of Pyrolysis Temperaturementioning
confidence: 94%
“…The temperature profile of the reactor was determined previously [20] and it was observed that the reactor is operated isothermally between 400 and 1000 mm sections.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods include gasification [3], hydrogenation [4], thermal and catalytic cracking [5,6], as well as the use of plastic wastes as a coke substitute in the steel industry. Among these methods, thermal cracking has been studied extensively [7][8][9][10][11]. The thermal degradation of polyolefins produces a mixture of hydrocarbons that is formed by gas (C 1 -C 4 ), liquid (C 5 -C 18 ) and waxy (C 18 -C 70 ) fractions.…”
Section: Introductionmentioning
confidence: 99%